(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Among infertile men, varicocele occurs in 25-35% of cases, and in men with secondary infertility - in 50-80% of cases. The causes of idiopathic varicocele can be one of 3 factors: increased pressure in the left renal vein, the presence of collateral venous anastomoses, the retrograde current through which increases pressure in the plexus, and insufficiency of the venous valves of the internal spermatic vein . The influence of varicocele on fertility is proved by the following provisions described by many researchers: high incidence of varicocele among infertile men, association of varicocele and pathological spermogram parameters , improvement of spermogram parameters after surgical treatment of varicocele.